A-016 The Relationship between Visual Memory and Performance in Virtual Reality Among Older Adults. (28th August 2020) - E, Flores; R, Gutierrez; S, Shorter; K, Mollenkopf; L, Childers; J, Flair; R, Donell; M, Barnett
Abstract: Objective: Over the past fifty years, many traditional paper-and-pencil neuropsychological tests have been translated to new computerized devices (Canini et al., 2014). Virtual reality offers neuropsychologists an opportunity to observe patients' neurocognitive functioning in an immersive, lifelike environment, rich in visual stimuli (Morganti, 2004), yet relatively little is known about the relationship between visual memory and performance on learning and memory tasks in virtual reality environments. The purpose of this study was to investigate, among older adults, the relationship between visual memory, as measured by a traditional paper-and-pencil test, and procedural learning and memory performance in a virtual reality environment simulating meal preparation tasks. Methods: Older adults (N = 73) ages 55-90 (M = 72.77, SD = 7.87) were administered the Weschler Adult Intelligence Scale-Fourth Edition (WMS-IV) Visual Reproduction Immediate Recall and the Virtual Kitchen Protocol (VPK), a virtual reality-based measure of learning and memory for meal preparation tasks. Results: Participants performance on the immediate portion of WMS-IV, visual reproduction, correlated with their performance on the VPK teaching trial (r = .65, p = 0.01), immediate recall (r = .51, p = 0.01), delayed recall (r = .58, p = 0.01), and forced choice recognition ( r = ..54, p = 0.01) of Job Sim. Conclusion: Results suggest that visual memory aids healthy older adults in procedural learning and memory tasks in the Virtual Kitchen Protocol, a virtual reality environment simulating meal preparation tasks. These results suggest that visual memory ability is germane to performance in virtual reality environments that are rich in visual stimuli.